Crowdfunding: um instrumento do consumo colaborativo = Crowdfunding: an instrument of collaborative consumption - Nunes, Geilson (2018)
Submitted by deniseoa@stj.jus.br (deniseoa@stj.jus.br) on 2018-01-10T18:42:06Z No. of bitstreams: 2 crowdfunding_instrumento_consumo_nunes.pdf: 1807127 bytes, checksum: b77272c870b8c16ef5ded4b059c0ed0c (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)